Chapter Literary Constellations. The Case of Armenian Authors Writing in Russian Today - Marchesini, Irina (Biblioteca di Studi Slavistici, 2018)
Reflecting on the concepts of 'transculturation' (Tlostanova 2004) and 'Russophonia' (Caffee 2013), this research concentrates on the contribution that writers of Armenian origin gave to the formation of the post-Soviet literary canon in Russia. This line of critical inquiry encourages a serious reflection on the role of the 'rossijane', and Armenians in particular, in the construction of contemporary Russian literature, an issue hitherto neglected in Russian Studies, as well as in Armenian Studies alike.